Model tests of consolidation of clay slurry using horizontal drains - Liu, Yixian (2017)
One of the widely used ground improvement approach is vacuum preloading with vertical drains. However, when this method is adopted for land reclamation using soft fill materials, it has limitations because it is difficult to install vertical drains over very soft deposits. To overcome this problem, a new land reclamation method using Prefabricated Horizontal Drains (PHD) has been developed. The objective of this project is to carry out large scale model tests to evaluate the performance of this proposed method.